2015
DOI: 10.1590/0104-07072015003610013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between drug dependence and alcohol users receiving treatment in a community health center specializing in alcohol treatment

Abstract: The aims of this study were: to identify the therapeutic activities of a psychosocial care center specifically for family members, and to consider whether the care offered provided benefits to the relationship between the family and alcohol users. This was a qualitative research study, and included 15 families of alcohol users from Minas Gerais. The data collection occurred during January and March of 2012. Thematic analysis was used. The analysis identified three themes: 1) relationship: before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
4
0
6
Order By: Relevance
“…Other than that, it consists in a place where the family can be taken care of and learn to look out for others and itself. 22,23 Scientific evidences stress that the family group meetings constitute empowering spaces and instrumentalization, offering them information, guidance and clarification upon psychoactive substance dependency, as well as competences and skills in handling the dependent at home. [23][24][25][26] The family support through friendships and the moment of the interview with the researches were relevant to the fortification of the family, for they constitute unburden, care and listening opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than that, it consists in a place where the family can be taken care of and learn to look out for others and itself. 22,23 Scientific evidences stress that the family group meetings constitute empowering spaces and instrumentalization, offering them information, guidance and clarification upon psychoactive substance dependency, as well as competences and skills in handling the dependent at home. [23][24][25][26] The family support through friendships and the moment of the interview with the researches were relevant to the fortification of the family, for they constitute unburden, care and listening opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Scientific evidences stress that the family group meetings constitute empowering spaces and instrumentalization, offering them information, guidance and clarification upon psychoactive substance dependency, as well as competences and skills in handling the dependent at home. [23][24][25][26] The family support through friendships and the moment of the interview with the researches were relevant to the fortification of the family, for they constitute unburden, care and listening opportunities. As a matter of fact, the informal social network and not professional can constitute important protecting factors by offering instrumental, emotional and community connection support to the family members, 6,20,27 as well as financial assistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a good example was presented in a study carried out at a Psychosocial Care Center for Alcohol and Other Drugs (CAPS AD -Centro de Atenção Psicossocial para Álcool e outras Drogas) in the state of Minas Gerais, which concluded that the proposal to give freedom for alcohol users' relatives to talk, discuss and being heard motivated them to attend the service. This led relatives to assume co-participation in the treatment of alcoholics, improving its functioning and a family adjustment (16) .…”
Section: Psychiatric Hospitalization Of Alcoholists From Rural Areas mentioning
confidence: 99%
“…The RAPS, and especially the CAPS, have increased throughout Brazil; however, the reality of mental health care in rural areas remains a problem. Thus, inhabitants of rural communities have problems accessing these services, whose organizational dynamics do not facilitate their participation in RAPS (16) .…”
Section: Psychiatric Hospitalization Of Alcoholists From Rural Areas mentioning
confidence: 99%
“…Apesar de a dependência química promover desequilíbrio intrafamiliar (1)(2) , a família pode se reorganizar e garantir o desenvolvimento de seus membros por meio do cuidado, afeto e da comunicação assertiva. Tal fato colabora para a adesão ao tratamento de seu parente (3)(4) , e para a prevenção e resolução dos problemas relacionados ao consumo de substâncias psicoativas por parte de um ou mais de seus membros (4) .…”
Section: Introductionunclassified